2020
DOI: 10.1108/intr-11-2019-0490
|View full text |Cite
|
Sign up to set email alerts
|

Roles of information propagation of Chinese microblogging users in epidemics: a crisis management perspective

Abstract: PurposeThe purpose of this research is to investigate the usage characteristics and the information propagation patterns of Chinese microblogs in different stages of an epidemic, given that the microblogging in China is different from other parts of the world. In addition, the authors aim to conceptualize the roles of different users and provide insights for using microblogging platforms to disseminate information in this context.Design/methodology/approachThe authors conducted an analysis on Sina Weibo microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In addition, the word frequency analysis of comments shows that both prevention and controlling measures are the main concerns in this stage. Therefore, in line with the literature in crisis management [20,68], the use of government social media in the acute stage should focus on providing up-to-date information and increasing transparency, regardless of the positive or negative nature of the content. The higher degree of sharing in the acute stage also indicates the potential of social media for disseminating information in a large scale, making it an effective tool for governments and authorities to broadcast updates during public health crises.…”
Section: Principal Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, the word frequency analysis of comments shows that both prevention and controlling measures are the main concerns in this stage. Therefore, in line with the literature in crisis management [20,68], the use of government social media in the acute stage should focus on providing up-to-date information and increasing transparency, regardless of the positive or negative nature of the content. The higher degree of sharing in the acute stage also indicates the potential of social media for disseminating information in a large scale, making it an effective tool for governments and authorities to broadcast updates during public health crises.…”
Section: Principal Resultsmentioning
confidence: 96%
“…In addition, other research highlights that government social media often carries only one-way communication in disease outbreaks [ 17 , 20 ], that is, messages are conveyed from governments to the public. Our data show that the public responded by leaving comments, which can be used as indicators for measuring the acceptance of certain policies in the pandemic and for fine-tuning them to meet the needs of people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Pourebrahim et al (2019) studied Twitter discussion of Hurricane Sandy and found that the connections between key influencers from different fields such as politics, news, weather and relief organizations and their followers played a crucial role in information sharing and dissemination, which provide an effective tool for emergency managers to establish two-way communication during disasters. Closely related to this study, Sun et al (2020) similarly studied the information dissemination patterns of Weibo during the African swine fever in 2018 and the results showed that different types of users play different roles, such as providing information, amplifying information, delivering information and engaging other users, and its beneficial for government agencies and public health authorities to effectively disseminate information.…”
Section: Literature Reviewmentioning
confidence: 67%
“…This reflects that the public actually used social media as a channel to provide feedback and suggestions to the government as the pandemic evolved. Research has found that governments tend to only carry out one-way communication (such as announcements) on social media [ 51 ], and such an approach is inappropriate and does not meet citizen expectations in times of crisis. During unprecedented times, public health responses need to adjust rapidly, and social media can serve as a probe to understand how society reacts to these responses.…”
Section: Discussionmentioning
confidence: 99%